Features of seasonal biogeochemical element migration in the "soil-plant" system: A case study of Bambusoideae in the Bidoup-Nui Ba National Park (Central Vietnam) - Pham, Cam Nhung; Lebedev, Yaroslav; Drygval , Anna; Gorbunov, Roman; Gorbunova, Tatiana; Kuznetsov, Andrei; Kuznetsova, Svetlana; Nguyen, Dang Hoi (Journal of Degraded and Mining Lands Management, 2024)
The article presents unique research conducted in Bidoup-Nui Ba National Park, Vietnam, focusing on the biogeochemical element migration in soil and plants. The study aimed to identify element content changes, biological accumulation, and biogeochemical mobility during wet and dry seasons across different landscape conditions. The research revealed the active elements involved in migration and accumulation, assessed mobility and accumulation in bamboo organs, and highlighted the peculiarities within the "soil-plant" system. The study found that the uptake of certain microelements by plants is influenced by landscape facies and moisture conditions. For example, Zn, Cu, and Co were introduced through plant litter during the wet season and accumulated, while Mo accumulation was more pronounced in the dry season. Furthermore, the research observed variations in biological uptake by bamboo organs, with different landscape conditions and seasons playing a role. The biogeochemical mobility of elements in bamboo organs increased significantly with soil moisture during the wet season. Overall, the research provided insights into element accumulation and biogeochemical migration. Notably, the accumulation of element B was found to increase with soil moisture, while its reduction was associated with slope process activation during the wet season.